eEF1A: Thinking Outside the Ribosome - Mateyak, Maria K. (American Society for Biochemistry and Molecular Biology, 2010)
Eukaryotic translation elongation factor 1A (eEF1A) is one of the most abundant protein synthesis factors. eEF1A is responsible for the delivery of all aminoacyl-tRNAs to the ribosome, aside from initiator and selenocysteine tRNAs. In addition to its roles in polypeptide chain elongation, unique cellular and viral activities have been attributed to eEF1A in eukaryotes from yeast to plants and mammals. From preliminary, speculative associations to well characterized biochemical and biological interactions, it is clear that eEF1A, of all the translation factors, has been ascribed the most functions outside of protein synthesis. A mechanistic understanding of these non-canonical functions of eEF1A will shed light on many important biological questions, including viral-host interaction, subcellular organization, and the integration of key cellular pathways.